2013
DOI: 10.1523/jneurosci.2087-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Role of Medial Prefrontal Cortex Serotonin 2A Receptors in the Control of Retrieval of Recognition Memory in Rats

Abstract: Often, retrieval cues are not uniquely related to one specific memory, which could lead to memory interference. Controlling interference is particularly important during episodic memory retrieval or when remembering specific events in a spatiotemporal context. Despite a clear involvement of prefrontal cortex (PFC) in episodic memory in human studies, information regarding the mechanisms and neurotransmitter systems in PFC involved in memory is scarce. Although the serotoninergic system has been linked to PFC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 76 publications
7
52
0
Order By: Relevance
“…Consistent with these observations and the critical role of presynaptic 5-HT 2A receptors in the induction of t-LTD, we found that 5-HT 2A −/− mice do not learn object-in-place associations, but show similar performance as WT mice in singleitem recognition or location recognition tasks. These results also corroborate a recent report, which showed that the perfusion of MDL 11939, a 5-HT 2A antagonist, into the PFC only alters objectin-place memory retrieval, but not single-item recognition (46). Such a phenotype was also induced by bilateral lesions not only in the PFC, but also in the MD nuclei, suggesting a complex interplay between both brain regions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with these observations and the critical role of presynaptic 5-HT 2A receptors in the induction of t-LTD, we found that 5-HT 2A −/− mice do not learn object-in-place associations, but show similar performance as WT mice in singleitem recognition or location recognition tasks. These results also corroborate a recent report, which showed that the perfusion of MDL 11939, a 5-HT 2A antagonist, into the PFC only alters objectin-place memory retrieval, but not single-item recognition (46). Such a phenotype was also induced by bilateral lesions not only in the PFC, but also in the MD nuclei, suggesting a complex interplay between both brain regions.…”
Section: Discussionsupporting
confidence: 91%
“…To (44,45) and in rodent models (46). Recently, the mPFC and MD nuclei were found to cooperate within an integrated neural circuit to support associative learning, a key feature of episodic memory, and disruption of the thalamocortical pathway impaired learning of object-in-place associations (47).…”
Section: Resultsmentioning
confidence: 99%
“…Although MDL 11,939 has low nanomolar affinity for 5-HT2a receptors it has a 150-fold higher affinity for 5-HT2a receptors than for 5-HT2c receptors in the rabbit, and a 300-fold and 4000-fold higher affinity in rats and humans, respectively (Aloyo & Harvey, 2000; Pehek et al, 2006; Wainscott et al, 1996). Second, although comparable data are limited the doses used here are within the range used by other studies that administered MDL 11,939 into the medial prefrontal cortex (Bekinschtein et al, 2013). Third, we have previously shown that systemic administration of MDL 11,939 reduces the acquisition of CD at doses that have been shown to not affect 5-HT2c receptors (Aloyo & Harvey, 2000; Harvey et al, 2004; Harvey et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, the current literature suggests that the OiC task relies on function of the hippocampal system in adult rats [12, 30, 34, 36, 38, 39], with a few exceptions [18, 37]. The disparate findings regarding the role of the hippocampus in OiC memory may reflect variable delays employed by different studies which differentially recruit short-term vs. long-term memory processes, or variation in the degree of spatial processing required for discrimination of the contexts during the task.…”
Section: Discussionmentioning
confidence: 99%